Bipolar dual-broadband photodetectors based on perovskite heterojunctions. Issue 2 (1st June 2022) - Li, Yu; Guo, Fumin; Yu, Shanshan; Wang, Jian; Yang, Shihe
Abstract: The development of efficient photodetectors for color recognition is of great importance for many applications. In this paper, we report a novel bipolar dual-broadband photodetector equipped with a perovskite heterojunction, with bidirectional broadband responses in the short-wavelength and long-wavelength regions at zero bias voltage, enabled by a charge separation reversion mechanism. The unique aerosol–liquid–solid technique allowed the perovskite heterojunction to be fabricated by successively depositing wide-bandgap perovskite (WBP) and narrow-bandgap perovskite (NBP) layers directly on the transparent substrate. For photodetectors based on the perovskite heterojunctions, the short-wavelength photons were depleted by the bottom WBP layer and generated negative responses, while the long-wavelength photons were absorbed by the top NBP layer and generated positive responses. Moreover, the demarcation wavelength between the bipolar responses and the cut-off wavelength can be easily tuned by adjusting the bandgaps (or compositions) of the bottom and top perovskite layers.